2018
DOI: 10.1590/s0100-204x2018000100012
|View full text |Cite
|
Sign up to set email alerts
|

Oral progesterone supplementation for beef cattle after insemination in TAI programs

Abstract: The objective of this work was to evaluate the effects of supplementation with melengestrol acetate (MGA), after timed artificial insemination (TAI), on the conception rate of Nellore cows, according to cyclicity during the protocol, estrus expression between intravaginal device withdrawal and insemination, and diameter of the largest follicle at the time of insemination, in order to identify predictors of the use of MGA. Multiparous lactating cows (577) were subjected to a hormonal protocol for ovulation sync… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
(30 reference statements)
0
4
0
4
Order By: Relevance
“…Os efeitos da suplementação de P4 sobre a fertilidade de bovinos tem sido bastante estudado, mas os resultados são inconsistentes, tendo resultados positivos (Loiola et al 2018), e negativos (Pugliesi et al, 2014a;Pugliesi et al, 2014b). No entanto, estes experimentos variaram em relação a categoria animal, método e dia da suplementação em relação a IA, via de administração e tipo de progesterona (sintética e natural).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Os efeitos da suplementação de P4 sobre a fertilidade de bovinos tem sido bastante estudado, mas os resultados são inconsistentes, tendo resultados positivos (Loiola et al 2018), e negativos (Pugliesi et al, 2014a;Pugliesi et al, 2014b). No entanto, estes experimentos variaram em relação a categoria animal, método e dia da suplementação em relação a IA, via de administração e tipo de progesterona (sintética e natural).…”
Section: Resultsunclassified
“…Taxa de gestação (%) em novilhas Nelore tratadas ou não com progesterona exógena pós-IA, de acordo com o diâmetro folicular no dia da IATF Loiola et al (2018). verificou que não houve diferenças entre folículos medianos e grandes em relação a taxa de prenhez, sendo ambas categorias diferentes significativamente (P<0,05) do que aquelas que apresentam folículos com <11 mm.…”
unclassified
“…Melengestrol acetate (MGA) is a synthetic progestational steroid supplied orally (Bertan et al, 2005;Sá Filho et al, 2007;Silva Junior et al, 2014) and acts to inhibit the pre-ovulatory LH (luteinizing hormone) peak similar to the action of progesterone produced by the corpus luteum (Imwalle et al, 2002). When added to the nutritional supplement provided to females, it is convenient because no individual management of animals is required for the administration (Loiola et al, 2018). The results obtained after using this progestin are still inconsistent because although some studies have shown no effect on pregnancy rates and even negative results when evaluated in relation to fertility (Yan et al, 2016), other studies reported an increase in pregnancy rates of cows in postpartum anestrus supplemented with MGA (Wood-Follis et al, 2004) and also in prepubertal heifers (Pfeifer et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Hormonal implants has been used by researchers to enhance growth, feed intake and reproductive efficiency in animals to satisfy the increasing demand of food supply [21]. Melengestrol (MGA) is available as a food additive for growth enhancement but approved only for used in beef heifers [22].…”
Section: Introductionmentioning
confidence: 99%